CULTURE MEDIUM KNUDSON MODIFIED UTILIZED IN VITRO CULTIVATION OF ORCHID’S HYBRID - SILVA, Enoque Fernandes da; VILLA, Fabíola; PASQUAL, Moacir (Scientia Agraria, 2009)
The genera Cattleya, Laelia and Brassavola occur naturally in Brazil and they are world wide wanted as ornate plants and that desire for them creates the necessity to develop better propagation’s techniques not only to attend the market needs but also to contribute to the replacement of the endangered species where they could become extinct. The explant’s origin and the culture medium where they are cultivated are determinative factors for plants tissue culture success. The purpose was to test Knudson culture media concentrations and MS media vitamins in orchid subcultive BC pastoral x LC Amber Glow. The current experiment was accomplished being used concentrations of Knudson media concentrations (0%, 50%, 100%, 150% and 200%) combined with MS media vitamins concentrations (0%, 50%, 100% and 200%). The explants used were from plantlets germinated in vitro with medium size 1 to 1.5 cm, submitted to the uniformization in Knudson media for three months. Its concluded that the increase in number of buds and leves of hybrid is not influenced with MS vitamin addition in the culture medium Knudson. The culture medium Knudson does not promote increase to radicular system. Vitamins of the MS added to culture medium are beneficial for good development of roots.